Intranodal lymphangiography under microsurgery for refractory lymphatic ascites after pelvic lymphadenectomy - Shota Higami; Yusuke Tanaka; Daisuke Maeda; Hiroshi Yukimoto; Tomomi Ishii; Yasuhiko Shiki (Elsevier, 2024)
Lymphatic ascites is a postoperative complication of lymph node dissection. Most symptomatic cases improve with conservative treatments. However, optimal management strategies for intractable lymphatic ascites remain controversial, and clinicians sometimes encounter intractable lymphatic ascites that does not respond to conservative management.We herein report a case of postoperative intractable lymphatic ascites that was successfully treated with intranodal lymphangiography (LG) from inguinal lymph nodes under microsurgery. A 56-year-old woman was diagnosed with stage II endometrial cancer and underwent total abdominal hysterectomy, bilateral salpingo-oophorectomy, and pelvic and para-aortic lymphadenectomies. On postoperative day (POD) 13, the patient presented with abdominal distention, and lymphatic ascites was diagnosed. Although the patient was treated with conservative management and lymphaticovenular anastomosis, her lymphatic ascites did not resolve. Finally, intranodal LG from the inguinal region was performed under microsurgery. A 2-cm incision was made on each side of the inguinal region. Once the lymph nodes were identified, a 23-gauge needle was inserted into the lymph node and lipiodol was injected. Extravasation of lipiodol into the abdomen from the left side of the lower pelvic region was confirmed. The postoperative course was uneventful. The ascites gradually decreased and disappeared within two weeks after LG.